The Improvement of Paclitaxel Cytotoxicity using Nanocellulose based Nature Resources - Nahrowi, R; Setiawan, A; Noviany, Noviany; Sukmana, I; Yuwono, S D (University of Lampung, 2019)
Paclitaxel is one of the cancer drugs that often used. These drug kills cancer cells byinhibiting mitotic cycle. The efficiency of paclitaxel is increased by the use ofnanomaterials as a carrier of paclitaxel. Nanomaterials can enhance encapsulationefficiency, improve the drug release to the target cell following nanomaterialdegradation, and improve local accumulation of drug in the cell through endocytosisreceptor. Nanomaterial that often used forencapsulation of paclitaxel is a polymerderived from natural resources such as cellulose. The advantages of cellulose as acarrier of paclitaxel are nontoxic, biodegradable, and very abundant from varioussources. One of the potential sources of cellulose for drug delivery system is cassavabaggase.Keywords: Paclitaxel, encapsulation, cell viability, nanocellulose